(untitled) (International Journal of Food and Nutritional Sciences, 2019)
In the realm of architecture, the intricate dance between design elements and human psychology unfolds a captivating narrative. Each facet, from materials and furniture to open spaces, temperature, and even room odors, plays a pivotal role in shaping individual moods and influencing the collective psyche.